Nyadran: Tradisi Penghormatan Leluhur dalam Bingkai Nilai-Nilai Islam di Dusun Silawan Desa Kutorojo - Rohman, Akhmad Dalil; Afiah, Karimatul; Riayana, Riayana; Huda, Muhammad Fathul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
The Nyadran Tradition in Silawan Hamlet, Kutorojo Village, Kajen Sub-district, Pekalongan Regency reflects the harmony between Islamic values and Javanese culture. This study aims to explore the Nyadran practice as a case study representing a creative adaptation to changing times and social solidarity in rural communities. A qualitative approach is employed, focusing on a case study, involving participatory observation and in-depth interviews. The research findings indicate that Nyadran is not merely a ritual of honoring ancestors but also an expression of the cultural richness and spirituality within the community. The harmonious integration of Islamic elements with local Javanese traditions not only strengthens religious and cultural identities but also enhances social solidarity and the values of mutual cooperation. Thus, Nyadran serves not only as a valuable symbol of cultural diversity but also enriches the understanding of the harmony between local traditions and religions in the lives of rural communities in Indonesia.